Comunicação, educação e consumo : a telenovela Lado a Lado e a questão do negro no Brasil - Barreto, Rosana Grangeiro (2017)
This is a study about the use of Brazilian television fiction in Junior High and High School classrooms. Our teledramaturgy presents and discusses the diversified Brazilian everyday life. The telenovela Lado a Lado (Side by Side, Globo, 2012/2013) showed the Brazilian modernization process during the first decades of the last century by focusing on the everyday lives of the people of Rio de Janeiro. The story discussed territorial disputes in the urban space, racism, African religion and culture, the integration of black people in society, among other topics. We argue that this particular work offers important resources for the debate on the question of black culture nowadays. It also allows us to reflect upon the shift of the hegemonic place of speech in historical narratives, as in Lado a Lado the narrators are the poor and black people. Our theoretical framework rests in the field of Communication/Education as well as in the studies of the interfaces Communication/Consumption. The media system takes part of the educational process, as discussed within the field Communication/Education. The media and the school systems are bound together with cultural consumption, a central practice in contemporary life. Our study aimed to comprehend the communicational interaction between school and the informal pedagogy of the telenovela. In the qualitative empirical study we undertook, we tried to establish a dialogue between the discourses in the plot and their reception by the teachers. We interviewed ten selected teachers from three schools in the city of São Paulo: a state school and two private schools. From these interviews, we were able to analyse the cultural consumption of these teachers and the ways they use the media in their classrooms, with emphasis on television. It was our idea to investigate how media consumption intertwines with the educational process by its regular presence in the everyday lives of teachers and students alike. We discussed the pedagogical potential of the telenovela and its approach within the school environment. We analysed how teachers receive and reinterpret this type of content in their practice. We sought to reflect upon the ways in which this work of fiction could complement the work of professionals who promote the construction of knowledge and of the critical sense in the formation of their young students. For most teachers, the school is the place for education, par excellence. They have a predominantly functionalist view of Communication and they worry greatly about the possible negative effects of the media on our youth. We understand that education plays a leading role in the construction of knowledge, which closely relates with the construction of citizenship. However, we argue that communication and cultural consumption also play a part in this process. In the complexity of today’s world, we conclude that reaching a balance point among the different social agents that form the current multifaceted educational ecosystem constitutes one of the main challenges in contemporary education.